Adipose derived mesenchymal stem cells seeded onto a decellularized nerve allograft enhances angiogenesis in a rat sciatic nerve defect model. Issue 5 (31st March 2020) - Mathot, Femke; Rbia, Nadia; Bishop, Allen T.; Hovius, Steven E. R.; Shin, Alexander Y.
Abstract: Purpose: Adipose derived mesenchymal stem cells (MSCs) are hypothesized to supplement tissues with growth factors essential for regeneration and neovascularization. The purpose of this study was to determine the effect of MSCs with respect to neoangiogenesis when seeded onto a decellularized nerve allograft in a rat sciatic nerve defect model. Methods: Allograft nerves were harvested from Sprague–Dawley rats and decellularized. MSCs were obtained from Lewis rats. 10 mm sciatic nerve defects in Lewis rats were reconstructed with reversed autograft nerves, decellularized allografts, decellularized allografts seeded with undifferentiated MSC or decellularized allografts seeded with differentiated MSCs. At 16 weeks, the vascular surface area and volume were evaluated. Results: The vascular surface area in normal nerves (34.9 ± 5.7%), autografts (29.5 ± 8.7%), allografts seeded with differentiated (38.9 ± 7.0%) and undifferentiated MSCs (29.2 ± 3.4%) did not significantly differ from each other. Unseeded allografts (21.2 ± 6.2%) had a significantly lower vascular surface area percentage than normal nonoperated nerves (13.7%, p = .001) and allografts seeded with differentiated MSCs (17.8%, p = .001). Although the vascular surface area was significantly correlated to the vascular volume ( r = .416; p = .008), no significant differences were found between groups concerning vascular volumes. The vascularization pattern in allografts seeded with MSCs consisted of an extensive nonaligned network of microvessels with a centripetal pattern, while the vessels in autografts and normal nerves were more longitudinally aligned with longitudinal inosculation patterns. Conclusions: Neoangiogenesis of decellularized allograft nerves was enhanced by stem cell seeding, in particular by differentiated MSCs. The pattern of vascularization was different between decellularized allograft nerves seeded with MSCs compared to autograft nerves.